Stages of change in the purchase of ultra-processed snacks among university students after the implementation of the chilean food law; a multi-center study - Durán Agüero, Samuel; Silva Rojas, Jaime; Caichac, Astrid; Araneda, Jacqueline; Rojas, Waleska Willson; Buhring, Rodrigo; Pacheco, Viviana; Encina, Claudia; Ahumada, Danay; Fernández-Salamanca, Marcelo; et al. (Archivos Latinoamericanos de Nutrición (ALAN), 2021)
The Objective is to determine the stages of change in the behavior of university students regarding the purchase of ultra-processed snacks consumed. Multi-center study (14 Chilean universities). The participants (4,807 students)evaluated were applied a survey to determine the stage of change of behavior regarding the purchase of foods with warning signs. The students were evaluated and classified as (a) Nutrition Students, (b) Healthcare-related Students and (c) Other degree Students. More than 90% of the students were aware of the food regulation and knew the warning signs. More than 60% of Healthcare-related and Other degree students are in the stage of pre-contemplation or contemplation regarding purchase intent of sugary drinks, juices, cookies, sweet snacks and potato chips; this value is twice the percentage of Nutrition students in this stages ( Chi2, p<0.001). In conclusion there is a high proportion of pre-contemplation and contemplation with respect to purchase intent among the students. Determinar las etapas de cambio en el comportamiento de los estudiantes universitarios con respecto a la compra de colaciones ultraprocesadas. Estudio Multicéntrico (14 universidades chilenas). A los participantes (4.807 estudiantes) se les aplicó una encuesta para determinar el cambio en el comportamiento con respecto a la compra de alimentos con sellos de advertencia. Los estudiantes se clasificaron como (a) estudiantes de nutrición, (b) estudiantes del área de la salud y (c) estudiantes de otras carreras.Se evaluaron. Más del 90% de los estudiantes conocían la regulación alimentaria y conocían las señales de advertencia. Más del 60% de los estudiantes de la salud y de otras carreras se encuentran en la etapa de pre-contemplación o contemplación con respecto a la intención de compra de bebidas azucaradas, jugos, galletas, bocadillos dulces y papas fritas; Este valor es el doble del porcentaje de estudiantes de nutrición en estas etapas ( Chi2, p <0,001). Se concluye que existe una alta proporción de pre-contemplación y contemplación con respecto a la intención de compra entre los estudiantes universitarios.